2006
DOI: 10.1016/j.cub.2006.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees use stone hammers in Cameroon

Abstract: BFU2004-02002) and by DURSI, Generalitat de Catalunya. We thank three anonymous referees for their comments and suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 7 publications
1
52
0
4
Order By: Relevance
“…Setting aside regional variations in behaviour that were likely explicable by environmental differences, this analysis identified 39 putative traditions. One of the clearest is the percussive activity of nut-cracking, which occurs across a swathe of far-west Africa about 700 km from north to south [13], but not in central or East Africa (an earlier report based on cracked nuts in Cameroon [26] remains unconfirmed). This behaviour appears robust with respect to the potential difficulty of reliably excluding environmental explanations for the differences documented: two independent expeditions to non-nut-cracking locations confirmed that the raw materials of nuts and suitable hammers were readily available [27,28].…”
Section: Experimental Studies Of Nut-cracking By Chimpanzees (A) Backmentioning
confidence: 99%
“…Setting aside regional variations in behaviour that were likely explicable by environmental differences, this analysis identified 39 putative traditions. One of the clearest is the percussive activity of nut-cracking, which occurs across a swathe of far-west Africa about 700 km from north to south [13], but not in central or East Africa (an earlier report based on cracked nuts in Cameroon [26] remains unconfirmed). This behaviour appears robust with respect to the potential difficulty of reliably excluding environmental explanations for the differences documented: two independent expeditions to non-nut-cracking locations confirmed that the raw materials of nuts and suitable hammers were readily available [27,28].…”
Section: Experimental Studies Of Nut-cracking By Chimpanzees (A) Backmentioning
confidence: 99%
“…Several lines of evidence now indicate that chimpanzees designated as P. t. ellioti have a unique epidemiological (12), cultural, and ecological heritage (39,40). However, morphological data for P. t. ellioti are very sparse, and the published studies are confounded by inclusion of specimens (41,42) collected outside its geographic range (6).…”
Section: Discussionmentioning
confidence: 97%
“…Chimpanzees in the wild are known to use natural stone and wooden hammers to crack open various nut species [14,30,[36][37][38][39][40]. Nut-cracking is a classic percussion behaviour whereby a nut is placed on a hard surface and a hammer is used to pound it until the nut breaks open.…”
Section: Introductionmentioning
confidence: 99%